Protection of piping systems subject to fires and explosions - Hamdan, Fadi (Steel Construction Institute, 2005)
This technical note provide a methodology on the design and the protection piping systems and piping supports on both offshore installations and onshore plants for fires and explosions.
Keywords: Offshore structures.; Piping -- Fires and fire prevention.; Explosions.; Structural analysis (Engineering); elektronické knihy; electronic books